Faktor-Faktor yang Mempengaruhi Kerjasama Jangka Panjang untuk Meningkatkan Keunggulan Kompetitif Perusahaan - Cahyono, Joko (Jurnal Ilmiah Aset, 2010)
The study was conducted in PT Meka Adipratama Semarang in which a turnover decline had been found due to the high business competition and the company’s inefficient channel of distribution. The research study was aimed at finding out reputation, trust, dependency, satisfaction, commitment, and communication factors towards long-term cooperations in order to develop the company’s competitive excellence. Questionnaires and interviews were used to learn about respondent’s perceptions on each variable. This is in accordance with type and data resource used, i.e primary data. Meanwhile, for the analysis technique, SEM with AMOS 5 program was applied to test the research model as well as the proposed hypothesis.The result shows empiric evidence that the variables used, i.e. reputation, trust, dependency, satisfaction, commitment and communication, have a positive and significant influence on long-term cooperations. By considering these factors, harmonious and beneficial cooperations can be achieved and the company’s competitive advantage can be enhanced. Both the limitation and future research agenda will be further explained in the last chapter of this study.